Emerging Knowledge from Sri Lanka Tamil Fiction for Sustainable Regional Development: A Study on Selected Pieces - Shriganeshan, K. (Eastern University, Sri Lanka, 2016)
Regional development requires mush of pre-planning and needs to consider various factors like available natural resource and the way they could be exploited with the knowledge available and emerging to look for some new development. However, destruction of the environment and natural resources is the main danger that the modern world has to face. There is an urgent need for institutional reform within modern society to safeguard the environmental resources and to maintain the ecological balance. Environmental sociologists have different views as to which institutional traits can be held primarily responsible for the environmental crisis. Further, there are other aspects like the effects of war- bereavement, loss habitat, displacement and exile which slows down the progress with regard to regional development of our country. The life in the latter part of the 20th Century became very mush painful and suffering due to the poor economic and deteriorating political conditions that prevailed in Sri Lanka. The traditional concepts of life held by the people further aggravated the people’s struggle for existence in the conflict-ridden parts of the country. The ignorance of the people and their fear psychosis led them to face more struggles to find a peaceful life. In order to understand the ground situation for planning for regional development there is a need to discuss what happened in the past especially during the war. The writers who faced the challenge have recorded their experience and the future agents could find suggestions for new development. The knowledge emerging out of the short stories under study would be helpful to go forwards towards regional development. The pieces written by Sri Lanka Tamil writers available in translation which appeared in Lute Song and Lament, A Lankan Mosaic, Tamil short stories from Sri Lanka are taken for critical analysis. This paper attempts to highlight the writers’ concern about the safety of the environment and the ecological balance of natural resource which could be the base for new understanding for sustainable development.
Keywords: Struggle; Challenges; Fcar psychsis